(Pb, Sm)(Zr, Sn, Ti)O3 Multifunctional Ceramics with Large Electric‐Field‐Induced Strain and High‐Energy Storage Density. Issue 12 (24th October 2016) - Zhang, Qingfeng; Chen, Jian; Lu, Yinmei; Yang, Tongqing; Yao, Xi; He, Yunbin
Abstract : Recently, the progress of integrated electronics has led to a strong demand for materials and devices with multiple functions. In this study, we achieved Pb0.985 Sm0.01 (Zr0.64 Sn0.28 Ti0.08 )O3 (PSZST) multifunctional ceramics which showed simultaneously large electric‐field‐induced strain (0.63%) and high recoverable energy density (1.743 J/cm 3 ) at room temperature. Moreover, the strain and recoverable energy density exhibited a slight frequency fluctuation in the frequency range of 1–10 Hz. Their variations were less than 8% and 1.3% and the values were all higher than 0.58% and 1.722 J/cm 3, respectively. The large strain, high‐energy density, and their good frequency stability in a wide range indicate that the PSZST ceramic is quite promising for application in multifunctional devices.